A Moradia como "Causa": uma análise do processo de afirmação de uma associação habitacional e de seus empreendedores políticos na região metropolitana de São Luís/MA - ALCOBAÇA, Luzinele Everton de (2017)
This study is related to the discussions about Militant Engagement and particularly deals with the affirmation process of a housing association and its political entrepreneurs in the São Luís metropolitan region. The emergence of this collective agent in 2003 was the local reflection of the change that occurred in the relationship between social movements and the government noticed in the period of redemocratization in Brazil. From this, we observed a relative degree of inclusion of popular sectors in political and administrative institutions. In the Luís Inácio Lula da Silva and Dilma Rousseff governments, the experiences so-called "participatory” have multiplied and become institutionalized. In this manner, social movement organizations activated the "right to the city," "urban reform," and "self-management" symbols have gained ground in planning and implementing housing estates for the grassroots in different parts of the country. In this context, the research attempted to comprehend how the State Association for Support of Popular Housing became representative of the "housing cause" in Maranhão and to trace its specificities, the delineations that such collective agent gave to the issue housing locally, realizing in the process the political role of representation and mediation of this mediator and his individual spokespersons. Thus, this research on a social organization and the militant engagement of its representatives was problematized from the perspective of historical sociology and militant engagement sociology, highlighting the social properties of those who engage, their accumulated attributes, resources detained, individual predispositions to militancy and, on a more general level, to the opportunity spheres and constraining under which this occurs. Considering the genetic, relational and sociographic perspective, the results were obtained through archival research, documentary, participant observation and interviews made with both the organization militants and some activists who graduated from this "problematic" in Maranhão in the first semester 2016.